Development of Trinidad and Tobago's first National Clinical and Policy Guidelines on Intimate Partner Violence and Sexual Violence - Nyla Lyons; Britta Baer; Natasha Sookhoo; Adesh Sirjusingh; Roma Bridgelal-Nagassar; Caroline Allen (Pan American Health Organization, 2024)
This Special Report aims to outline the development process of the first National Clinical and Policy guidelines on Intimate Partner Violence and Sexual Violence in Trinidad and Tobago and to support the implementation of quality standards for survivors. The study used an implementation science approach to identify key evidence-based practice recommendations from guidance documents on health care for women who are subjected to violence and from relevant national legislation, policy, and practices. The process engaged stakeholders in discussions on the appropriateness, implementation, and use of these recommendations in the context of local health care delivery. Multidisciplinary teams of frontline health workers were consulted in groups in each of the five Regional Health Authorities. Interviews were held with senior government stakeholders responsible for health policy and with representatives of four civil society agencies. Participants provided recommendations to integrate quality standards into routine practice. These were incorporated into the guidelines, which include human rights principles and pathways of care for identifying violence, providing psychosocial and clinical care, safety planning, referrals, care during emergencies, and prevention of intimate partner violence and sexual violence. The guidelines were approved by the Ministry of Health of Trinidad and Tobago on 15 August 2022. Training of trainers has been undertaken to support implementation.